Ductal obstruction promotes formation of preneoplastic lesions from the pancreatic ductal compartment - Cheng, Tao; Zhang, Zhiheng; Jian, Ziying; Raulefs, Susanne; Schlitter, Anna Melissa; Steiger, Katja; Maeritz, Nadja; Zhao, Yamin; Shen, Shanshan; Zou, Xiaoping; Ceyhan, Güralp Onur; Friess, Helmut; et al. (International journal of cancer, 2019)
Pancreatic cancer, pancreatitis, ductal obstruction, ADM, TC